Artificial intelligence and central bank communication: The case of the ECB - Nicolas Fanta; Roman Horváth (Charles University in Prague, Institute of Economic Studies (IES), 2023)
We examine whether artificial intelligence (AI) can decipher European Central Bank's communication. Employing 1769 inter-meeting verbal communication events of the European Central Bank's Governing Council members, we construct an AI-based indicator evaluating whether communication is leaning towards easing, tightening or maintaining the monetary policy stance. We find that our AI-based indicator replicates well similar indicators based on human expert judgment but at much higher speed and at much lower costs. Using our AI-based indicator and a number of robustness checks, our regression results show that ECB communication matters for the future monetary policy even after controlling for financial market expectations and lagged monetary policy decisions.
Keywords: E52; E58; 330; Artificial intelligence; central bank communication; monetary policy